The rise and progress of printing - Allen, Amy Alena (My University, 1904)
Introduction: 1. Definition: Printing is the art of taking an impression from an inked form, plate, block or stone. 2. Branches: There are several distinct branches of this important art, and each branch is, practically, a separate art, distinct from its rivals in its theory, its processes, and its applications. These methods are: (a) Steel-plate and Copper-plate Printing, in which the subject is printed from an etching or engraving below the surface of a plate of steel or copper. (b) Lithography, in which the subject is printed from a transferred engraving on the surface of a prepared stone.(c) Xylography, in which the subject is printed from a design engraved on a block of wood in high relief. (d) Typography, in which the subject is printed from a combination of movable metal types cast in high relief. The arts of lithography and copper-plate are useful and beautiful methods of printing, but they do not make books and newspapers. The necessity which compels the making of a new engraving for every new subject restricts them almost exclusively to the field of art and ornament. If no other method of printing were known, encyclopedias and newspapers would be impossibilities. "The art preservative of all arts" is not the art of lithography nor of copper-plate. This distinction rightfully belongs to typography only.
Citation: Allen, Amy Alena. The rise and progress of printing. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Printing; Technological Advancement; Technology; Publishing; Theses